Pengaruh Tipe Kepemilikan Ultima Keluarga dan Negara Terhadap Risiko Likuiditas Bank - Fadli, Jul Aidil; Sakti, Imanuel Madea (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
This research aims to examine the effects of family and state bank ownership on bank liquidity risk. The 20% ownership threshold determines the type of ownership, and the robustness test determined by the 25% ownership threshold, then bank liquidity risk is measured by Loan to Deposit Ratio (LDR). This study also used bank size to measure total bank assets, dummy listed or non-listed banks on the Indonesia Stock Exchange, and Capital Adequacy Ratio (CAR) as a measure of bank capital. The data used in this research are panel data of 59 commercial banks operated in Indonesia since 2010 to 2016. Using multiple linear regression analysis with Generalized Least Square estimation, the result shows that banks owned by family or state have lower liquidity risk than banks that do not belong to family or state. This research can be a reference for The Financial Services Authority and Indonesia Deposit Insurance Corporation to establish strategies and regulations related to bank  liquidity risk.